The Influence of Attitude and Supervision on Medical Waste Management Compliance with Waste Management Facilities as a Mediation Variable at Cibinong Hospital - Afraimansyah, Afraimansyah; Hilmy, Reza; Nofierni, Nofierni (Syntax Corporation, 2026)
Background: Non-optimal management of medical waste in hospitals has the potential to increase the risk of infections related to health services and environmental pollution. At Cibinong Hospital, non-compliance by officers in sorting, using personal protective equipment, and waste disposal is still found in accordance with standard operating procedures. Objective: This study aims to analyze the influence of attitude and supervision on compliance with medical waste management with waste management facilities as a mediating variable. Methods: The study used a quantitative approach with a cross-sectional design. The research population is health workers who are directly involved in the management of medical waste, with data collection using questionnaires that have been tested for validity and reliability. Data analysis was carried out using linear regression and path analysis to test the direct and indirect influence between variables. Results: The results showed that attitudes, supervision, and facilities simultaneously had a significant effect on compliance (p<0.001). Partially, attitude was the most dominant variable with a beta coefficient of 0.657. Waste management facilities have been proven to mediate the influence of attitudes and supervision on compliance. The research model was able to explain 58% of the variation in compliance. Conclusion: It was concluded that compliance was influenced by internal motivation and external reinforcement supported by the availability of facilities as the main enabling factor.